Analisis Manajemen Risiko Dampak Penggunaan Aplikasi TikTok pada Gen Z - Randis Wahyuni; Lucky Marsella; Lindha Juniarta Suseno; Miftahul Hasanah (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
TikTok is one of the most popular social media among teenagers, especially Generation Z. By having many advantages and attractive features, using Tiktok also has several impacts or risks that need to be managed properly. This study aims to analyze the risk management impact of using the TikTok application on Generation Z. The research method used is a literature study, online surveys and implementing five steps of risk management, namely; a) Avoidance, b) Retention, c) Sharing, d) Transferring, e) Loss Prevention and Reduction . The survey results show that most of the respondents are aware of potential risks in using the application. The identified risks include data privacy, cyberbullying, digital dependency, negative content, and copyright infringement. To overcome this, companies that own applications must strengthen their security systems and improve content filters so that they do not contain negative or dangerous elements for their users. In addition, parents must also be more proactive in escorting their children when using social media such as Tiktok and actively educate them about the dangers of using it.